The Great Irish Famine in Songs - Erick Falc’her-Poyroux (Revue Française de Civilisation Britannique, 2014)
Though fairly few Irish folk songs deal with the Great Famine and while the authenticity of those that remain cannot always be guaranteed, they nonetheless constitute valuable contemporary sources on the Famine from the perspective of ordinary people. The insights they provide as to the way they reacted to government measures, hunger, evictions and emigration are a useful complement to scholarly histories which sometimes neglect the human dimension of the Famine.